On the Road to ‘Some’ Place: Sofia Coppola’s Dissident Modernism Against a Postmodern Landscape - Todd Kennedy (Miscelánea: A Journal of English and American Studies, 2015)
Sofia Coppola’s enigmatic film, Somewhere, has met with conflicting responses from critics who attempt to label it a “European” film. Yet, as I argue, the film may be best understood not in its relationship to European cinema, but, rather, its relation to philosophical debates between modernism and postmodernism, to American film history, and, even more importantly, to one of the oldest and most dominant tropes in US culture —that of the hobo-hero. I begin by explaining the background of the figure of the hobo-hero, and its relationship to modernism, and then return to look at the manner in which Coppola draws upon this image in order to invoke (and comment upon) American identity, the postmodern culture of Los Angeles/Hollywood, and questions that are central to the discourse of philosophical modernism. Towards the end of the article, I draw upon the work of Marshall Berman in order to question whether there is a way in which the hobo-hero can allow modernism to openly defy postmodernism itself, even while expressing and exploring a postmodern landscape, a postmodern world. Perhaps surprisingly, I argue that such a question may be best answered by Sofia Coppola’s fourth feature film.